Pengembangan Model Manajemen Kurikulum Berbasis Penguatan Pendidikan Karakter untuk Meningkatkan Mutu Pembelajaran di Sekolah Dasar - Deri Nopita Sari (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to develop a curriculum management model based on character education strengthening that can be effectively implemented in elementary schools to improve the quality of learning. The background of this research is rooted in the declining quality of learning and the weakening of students’ character, indicating that character values have not been optimally integrated into basic education. A curriculum that focuses solely on cognitive aspects without considering students’ attitudes and behavior is no longer relevant in today’s educational context. Therefore, a curriculum management model that balances academic performance with character development is urgently needed. This study employed a Research and Development (R&D) method using both qualitative and quantitative approaches. The development procedures included needs analysis, initial model design, expert validation, field testing, and final model revision. The results of the study indicate that the developed model enhances teachers' roles in implementing character-based learning, strengthens positive school culture, and improves student learning outcomes both academically and affectively. The model also shows flexibility in adapting to the national curriculum and Islamic values within the Integrated Islamic Elementary School context. This research recommends the model as a practical reference for school principals and curriculum designers to formulate more meaningful and long-term impactful educational policies for students.